The Prevalence and Risk Factors of Acute Kidney Injury during Colistin Therapy: A Retrospective Cohort Study from Lebanon - Rima Moghnieh; Rola Husni; Mariana Helou; Dania Abdallah; Loubna Sinno; Marwa Jadayel; Kawsar Diab; Carmen Chami; Marah Al Rachid; Diana Caroline Awad; Aline Zaiter; Mohamed H. Sayegh (MDPI AG, 2023)
Introduction: The current study aimed to determine the prevalence, risk factors, and stages of severity of acute kidney injury (AKI) caused by colistimethate sodium (CMS) treatment in patients diagnosed with systemic antibiotic-resistant Gram-negative bacterial infections. The predictors of all-cause mortality in this patient population were also examined. Methods: This retrospective cohort study included patients who were admitted to a university-affiliated hospital and acute tertiary care referral center in Beirut, Lebanon between January 2015 and December 2018 and underwent CMS treatment for a period of 48 h or more. Results: The study sample included 298 adult patients, of which 46.3% (n = 138/298) developed AKI (assessed using the Kidney Disease Improving Global Outcomes (KDIGO) criteria). Of these, 37.7% (n = 51/138) were diagnosed with stage 1 AKI, 23.9% with stage 2 (n = 33/138), and 38.4% with stage 3 (n = 53/138). Nephrotoxicity was reversed in 87.5% of AKI patients who survived until hospital discharge. Independent risk factors for AKI included patient age ≥ 75 years (aOR = 1.854; 95% CI: 1.060-3.241; p-value = 0.03); underlying chronic kidney disease (aOR = 4.849; 95% CI: 2.618-9.264; p-value < 0.0001); and concomitant use of vasopressors (aOR = 4.305; 95% CI: 2.517-7.456; p-value < 0.0001). Multivariate analysis showed that the predictors of severe AKI (stage 2 or 3) included baseline hypoalbuminemia (aOR = 2.542; 95% CI: 1.000-6.564; p-value = 0.05); concomitant use of vasopressors (aOR = 6.396; 95% CI: 2.741-15.87; p-value < 0.0001); and CMS days of therapy (DOT) prior to development of AKI ≥ 7 days (aOR = 4.728; 95% CI: 2.069-11.60; p-value < 0.0001). All-cause mortality was recorded in 51.3% of patients (n = 153/298), and this was significantly higher in patients with AKI (76.8%; n = 106/138) compared to those without (29.4%; n = 47/160; OR = 7.964; 95% CI: 4.727-13.417; p-value < 0.0001). Independent predictors of all-cause mortality included a baseline Charlson comorbidity index score ≥5 (aOR = 4.514; 95% CI: 2.443-8.530; p-value < 0.0001); concomitant use of vasopressors (aOR = 7.76; 95% CI: 4.238-14.56; p-value < 0.0001); and CMS-induced AKI (aOR = 4.117; 95% CI: 2.231-7.695; p-value < 0.0001). Conclusions: The findings of this study suggest that old age, history of chronic kidney disease, and concomitant vasopressor treatment are all independent predictors of CMS-induced AKI. The risk of developing severe AKI significantly increases with CMS DOT. Understanding the risk factors of nephrotoxicity is essential for improving prognosis and treatment outcomes.